Memahami Strategi Pemasaran Online dalam Meningkatkan Keuntungan dengan Pengeluaran Efisien - Muhammad Dimas; Muhammad Irwan Padli Nasution (Jurnal Manajemen Riset Inovasi, 2024)
In the rapidly developing digital era, online businesses face increasing challenges to achieve significant profits without sacrificing spending efficiency. To overcome this challenge, an optimal online marketing strategy is needed that can reach the right target market without significantly increasing operational costs. This journal discusses several online marketing strategies that are effective in increasing profits relevant to expenditure. From a deep understanding of the target market to the use of social media and careful data analysis, every step taken is based on the principles of efficiency and effectiveness. By implementing the right marketing strategies, businesses can increase their visibility online, attract more potential customers, and increase sales conversions without having to exceed their available budget. Thus, this journal provides practical guidance for business owners and marketers to achieve success in their online sales without sacrificing profitability.